Reflections on the search for fertility effects on happiness - Øystein Kravdal (University of Oslo, Department of Economics, 2013)
There have been many studies of how the number of children in a family affects the parents' or the children's lives. One strand of this research focuses on the implications of fertility for the parents' level of self-reported well-being or happiness. It is argued in this paper that an overall happiness effect is not very informative because of the presumably large variation in individuals' perceived gains from having children. Furthermore, it is explained that such an effect would be difficult to estimate. Most importantly, the highly varying ideas about how a child will affect life quality are important for the decision about whether to have a child. Many of those who have few or no children have chosen this because they think their life will be best this way, and their happiness therefore tells us little about how happy their more fertile counterparts - who to a large extent have other preferences - would have been if they had few or no children. This estimation problem that arises because expectations about the effects of a certain behaviour (here childbearing) are heterogenous, and also affect that very behaviour, is acknowledged in the economics literature, but there is little consciousness about it in the fertility-happiness research. In addition, there is a more standard selection problem: factors with implications for childbearing desires, or for the chance of fulfilling these, may also affect or be linked to happiness for other reasons. Unfortunately, even the most advanced statistical approaches that have been used in this research area fail to handle all these problems, so reported results should be interpreted very cautiously.
Keywords: J13; 330; fertility; happiness; effect heterogeneity; method; selection; subjective well-being